2023
DOI: 10.3390/polym15112573
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Reinforced Poly(vinyl alcohol) Nanocomposites Doped with Silver-Loaded Zeolite L Nanoparticles as Sustainable Materials for Packaging Applications

Abstract: The sustainable development of innovative eco-friendly multifunctional nanocomposites, possessing superior characteristics, is a noteworthy topic. Novel semi-interpenetrated nanocomposite films based on poly(vinyl alcohol) covalently and thermally crosslinked with oxalic acid (OA), reinforced with a novel organophosphorus flame retardant (PFR-4) derived from co-polycondensation in solution reaction of equimolar amounts of co-monomers, namely, bis((6-oxido-6H-dibenz[c,e][1,2]oxaphosphorinyl)-(4-hydroxyaniline)-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…The chemical structure of resulting PVA composite films was investigated by FTIR spectroscopy (Figure 2). Such type of oxalic acid-reinforced PVA composites have been described also in our recent study [35]. The neat PVA-0 showed characteristic absorption bands at 3370 cm −1 (O-H stretching vibrations), 2937 and 2908 cm −1 (aliphatic C-H asymmetric and symmetrical stretching vibrations), 1736 and 1711 cm −1 (belong to residual acetyl groups remaining in fully hydrolyzed PVA), 1424 and 924 cm −1 (CH 2 bending and rocking).…”
Section: Structural and Morphological Characterization Of Pva Compositessupporting
confidence: 78%
“…The chemical structure of resulting PVA composite films was investigated by FTIR spectroscopy (Figure 2). Such type of oxalic acid-reinforced PVA composites have been described also in our recent study [35]. The neat PVA-0 showed characteristic absorption bands at 3370 cm −1 (O-H stretching vibrations), 2937 and 2908 cm −1 (aliphatic C-H asymmetric and symmetrical stretching vibrations), 1736 and 1711 cm −1 (belong to residual acetyl groups remaining in fully hydrolyzed PVA), 1424 and 924 cm −1 (CH 2 bending and rocking).…”
Section: Structural and Morphological Characterization Of Pva Compositessupporting
confidence: 78%
“…It is widely reported that zeolite-and clay-based materials can serve as carriers for silver ions [12][13][14]. Zeolite carriers possess a framework of silicate with high adsorption and ion exchange capabilities, which permits them to act as inorganic reservoirs for silver ions [15][16][17][18]. N. Torkian et al employed modified zeolite as a silver ion carrier to produce a Ag-ion-exchanged nanocomposite and successfully applied it in antibacterial applications [18].…”
Section: Introductionmentioning
confidence: 99%